Deep cutaneous phaeohyphomycosis caused by Cladophialophora boppii: A case report - Thuy Thanh Cavens; Janneke de Vries; Suzanne Verleisdonk-Bolhaar; Jochem B. Buil; Arienne van Marion (Medical Mycology Case Reports, 2025)
Cladophialophora boppii is a dematiaceous fungus rarely causing cutaneous and respiratory infections. We present a case of deep cutaneous infection in a 69-year-old patient in the Netherlands with stage IV breast cancer on dexamethasone therapy. The patient exhibited a skin plaque lesion, and biopsy revealed pigmented, septate hyphae without muriform cells, consistent with a diagnosis of phaeohyphomycosis. Surgical excision and culture confirmed C. boppii. Afterwards the patient received a three-week course of itraconazole, which led to infection resolution. This report and review of literature underscores the diagnostic and therapeutic approaches for managing deep cutaneous infections caused by C. boppii.